An analytical evaluation of information visualization factors for multiple electronic health records - Malik, M.S.A. (Institute of Electrical and Electronics Engineers Inc., 2016)
Information Visualization (IV) facilitate the robust understanding and efficient utilization of multiple Electronic Health Records (EHR) by all stakeholders such as Doctors, DBA and Visual Designers. Currently all IV models and tools focus on feedback from doctors while health informatics applications involves the collaboration of multidisciplinary professionals. IV model CARE 1.0 categorizes the IV factors in knowledge, skills, assessment and future perspective. This research paper presents the analysis of three questionnaire based studies from three stakeholders doctors, DBA and visual designers involved with the visualization of multiple EHR. Statistical results of the studies emphasize the inter relationships between knowledge, skills, assessment and future perspective for stakeholders. Â© 2016 IEEE.